Myocardial blood flow, oxygen consumption, and fatty acid uptake in endurance athletes during insulin stimulation - Takala, T. O.; Nuutila, P.; Katoh, C.; Luotolahti, M.; Bergman, J.; Maki, M.; Oikonen, V.; Ruotsalainen, U.; Gronroos, T.; Haaparanta, M.; Kapanen, J.; Knuuti, J. (American Journal of Physiology, Endocrinology and Metabolism, 1999)
We have previously demonstrated reduced myocardial glucose uptake rates in hearts of endurance athletes, which could be due to increased use of alternative fuels or reduced energy demands. In the present study myocardial blood flow, oxygen consumption, and free fatty acid uptake were measured with [(15)O]H(2)O, [(15)O]O(2), [(18)F]FTHA, and positron emission tomography (PET) in 9 endurance athletes and 11 sedentary men during euglycemic hyperinsulinemia. Compared with sedentary men, athletes had 33% lower myocardial blood flow, 27% lower oxygen consumption, and 20% lower estimated myocardial work per gram of tissue. Myocardial fatty acid uptake rates were not significantly different in endurance athletes (0.83 +/- 0.29) and sedentary men (1.0 +/- 0.31 micromol. 100 g(-1). min(-1), P = 0.232). In conclusion, myocardial blood flow and oxygen consumption per unit mass of myocardium are reduced at rest in endurance athletes. This can be explained by reduced energy requirements per gram of tissue due to anatomic and physiological changes of the athlete's heart.